SUPPLY CHAIN MANAGEMENT IN THE DEVELOPMENT OF MICRO, SMALL AND MEDIUM ENTERPRISES COMPETITIVENESS OF PROCESSED FOOD - Ariharti, Mira Astuti; Hubeis, Musa; Suryahadi, Suryahadi (Universitas Brawijaya, Indonesia, 2017)
this study aims to identify factors that affect the internal and external Supply Chain Management (SCM), Supply Chain analyze raw materials, systems of production and distribution of products, SCM appropriate strategy for SMEs. The method used in this study is descriptive analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), the analysis Internal External (IE), the analysis of Strengths, Weaknesses, Opportunities, and Threats (SWOT) and Quantitative Strategic Planning Matrix (QSPM). The number of respondents in this study at 15 institutions established by purposive sampling technique. The results of observations elected five SMEs Processed Food of Sambal. IFE matrix visible strength of production capacity per day which is owned SMEs can overcome the weaknesses of human resources quality elements quite well. While the total score of the matrix EFE (2.435) showed SMEs were able to respond to opportunities distribution network of products on line and minimize the threat of raw material price fluctuations, as well as the position of SMEs Processed Food of Sambal on IE matrix, is in quadrant V, namely to preserve and defend by using strategies market penetration and product development. SCM development strategy according to the results of the analysis and SWOT matrix QSPM generate a key strategic priority, namely inventory management effective and efficient methods First in First out (FIFO) and facilitated by the distribution network of products on line.